The South between Two Frontiers: Confederate Cowboys and Savage Rednecks - Hervé Mayer (Revue LISA)
The myth of the Frontier, which locates the birth of the American nation in its confrontation with a bordering savagery, was a national myth in Western films until the 1960s. As a genre engaged with the exploration of Americanness, the Western attracted many ex-Confederates in search of political legitimacy and the Western Frontier became a place of national rehabilitation for the South. When the narrative of the myth inverted in favor of the Indian in the late 1960s, freedmen replaced Confederate heroes in their quest to integrate the national community on screen. The Frontier as America’s birthplace gave the South a second chance and revealed its cultural potential for the nation. But the Frontier, in its confrontational version of the savage wars, also resonates with the myth of the Lost Cause, in which barbarous freedmen threaten white society. If The Birth of a Nation was the first and last film in which Blacks were pictured as predatory beasts in Hollywood, this internal frontier reappears with the cultural crisis of the 1960s, when the South became home to savages of a new kind, degenerate rednecks, who embody the failure of the national myth in the Western, serving as scapegoats for an American savagery revealed by the My Lai massacre and the Manson murders. The South in film thus wavers between two frontiers: the Frontier of American regeneration in the Western and the frontier as a threat to America in the Southern.